Christian ethics in post-apartheid South Africa – a Reformed perspective - Koopman, NN (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This paper portrays the ethical challenges facing South Africans in the post-apartheid era. I argue that The Confession of Belhar 1986 (hereafter referred to as Belhar) plays an illuminating role in describing these challenges as well as in suggesting ways in which South African churches can respond to them. The paper is structured as follows. In a first round the origins of Belhar is sketched (a). Thereafter (b) the significance of the five articles of Belhar (1-5) for identifying, describing and showing ways to address the ethical challenges facing South African churches is indicated. Opposition to deism, agnosticism, disunity, alienation, injustice and wrong loyalties is strongly pleaded for. The paper concludes (c) with general remarks about the significance of Belhar for the ethical task of South African churches, especially Reformed churches.